2008
DOI: 10.1186/1472-6963-8-203
|View full text |Cite
|
Sign up to set email alerts
|

Urban women's socioeconomic status, health service needs and utilization in the four weeks after postpartum hospital discharge: findings of a Canadian cross-sectional survey

Abstract: Background: Postpartum women who experience socioeconomic disadvantage are at higher risk for poor health outcomes than more advantaged postpartum women, and may benefit from access to community based postpartum health services. This study examined socioeconomically disadvantaged (SED) postpartum women's health, and health service needs and utilization patterns in the first four weeks post hospital discharge, and compared them to more socioeconomically advantaged (SEA) postpartum women's health, health service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
2
31
2
1
Order By: Relevance
“…In contrast to our study, distance and travelling time from home to RH services remain important barriers in rural areas of Nepal, the Philippines and Malawi [26,33,34]. Low accessibility to RH services among the poor youths due to a lack of affordability in our study highlighted the inequity of access to RH services between the rich and the poor, and the rural and urban dwellers as found in previous studies [8,35,36]. In addition, our study confirmed the finding from other studies that low accessibility to RH services results in low utilization of those services [25,26,37,38].…”
Section: Discussioncontrasting
confidence: 89%
“…In contrast to our study, distance and travelling time from home to RH services remain important barriers in rural areas of Nepal, the Philippines and Malawi [26,33,34]. Low accessibility to RH services among the poor youths due to a lack of affordability in our study highlighted the inequity of access to RH services between the rich and the poor, and the rural and urban dwellers as found in previous studies [8,35,36]. In addition, our study confirmed the finding from other studies that low accessibility to RH services results in low utilization of those services [25,26,37,38].…”
Section: Discussioncontrasting
confidence: 89%
“…Many studies have focused attention on how health care practices based on Western cultural concepts influence the ways in which immigrant women use mental health care services. Others have examined immigrant women’s perspectives about their social support preferences, the barriers they experience and their preferred support interventions [13,14]; moreover, difficulties may arise in relation to access to services and patterns of help-seeking [15], including language barriers, stigma-related concerns and discriminatory practices [6]. Furthermore, in Canada the Edinburgh Postnatal Depression Scale (EPDS) is widely used to screen for PPD despite the fact that it may not have cultural congruence for all ethnocultural groups [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear need to integrate this existing evidence base. Evolving from foundational research that we have conducted internation-ally, nationally and provincially, our review will establish the veracity of suggestions that existing mental health services might not provide appropriate support to women with PPD [13,14,17]. The complex factors that affect the lives of immigrant women and their preferences for postpartum health care and treatment need to be understood before appropriate measures can be taken to correct the current inability to reach these women [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…La evidencia cualitativa en países desarrollados destaca la relevancia que el personal de salud establezca vínculos positivos para la apertura de problemas emocionales, puntualizando la ventaja que supone la continuidad en los cuidados de la salud materno-infantiles para construir este vínculo 24,25 . Las barreras estructurales de accesibilidad 29,30 y la conciliación de exigencias contrapuestas 29,31,32 han sido documentadas principalmente en madres vulnerables socialmente, según la literatura internacional. La disponibilidad de horas y tiempos de espera extensos han sido referidas como características del sistema de salud que obstaculizan el acceso y la adherencia al tratamiento 11,24 .…”
Section: Discussionunclassified